ANALISIS KESULITAN MEMBACA PERMULAAN SISWA PADA KELAS I SDN CINDEREJO SURAKARTA - Aliyati, Yeni (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2024)
The aim of this research is to analyze the factors that inhibit beginning reading in grade 1 students at SDN Cinderejo and the alternatives used to overcome difficulties in beginning reading. The research method in this study is qualitative using a case study approach. The instruments used were teacher observation sheets, student observation sheets, and interview guides. The data collection techniques used were observation, interviews and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of the research show that the factors inhibiting beginning reading in grade 1 students at SDN Cinderejo include: 1). Intellectual Factors, 2). Environmental factors, 3). Lack of motivation from the family 4). Lack of student interest in reading. Meanwhile, alternative solutions that can be used to overcome difficulties in beginning reading are: 1). Class teachers prioritize children who experience difficulties, 2). Class teachers must also pay special attention to children who experience difficulties, 3). Good cooperative relationship between class teachers and students' parents 4). Parents must pay more attention and monitor children in learning to read, 5). Students' interests must be developed and trained continuously. The results of this research can be used as improvements and to improve the quality of learning which can develop the interests and abilities of low grade students in reading skills. Keywords: Beginning Reading, Elementary School, Difficulties